2015
DOI: 10.1007/s40502-015-0170-7
|View full text |Cite
|
Sign up to set email alerts
|

Major essential oil constituents, total phenolics and flavonoids content and antioxidant activity of Salvia officinalis plant in response to nano-titanium dioxide

Abstract: Medicinal plants produce a wide range of secondary metabolites to increase their performance upon exposure to various kinds of elicitors. The present study was undertaken to evaluate the impacts of various concentrations of nano-titanium dioxide (TiO 2 ) particles, viz., 0, 10, 50, 100, 200 and 1000 mg l -1 on growth, biosynthesis of secondary metabolites such as essential oils, total phenolics, flavonoids and antioxidant efficacy of the extracts obtained from the treated Salvia officinalis plants, assayed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 24 publications
7
34
0
Order By: Relevance
“…Considering the importance of its essential oils, any treatment with positive effects on its essential oil content and dominant constituents could be of great value to growers. The positive effect of TiO 2 NPs was previously reported in Salvia officinalis essential oil content and constituents 55 . Taking into account these factors, the current study examined the effect on Moldavian balm under normal and salt stress conditions.…”
Section: Assessment Of Biochemical Traits Evaluation Of Hydrogen Persupporting
confidence: 57%
See 1 more Smart Citation
“…Considering the importance of its essential oils, any treatment with positive effects on its essential oil content and dominant constituents could be of great value to growers. The positive effect of TiO 2 NPs was previously reported in Salvia officinalis essential oil content and constituents 55 . Taking into account these factors, the current study examined the effect on Moldavian balm under normal and salt stress conditions.…”
Section: Assessment Of Biochemical Traits Evaluation Of Hydrogen Persupporting
confidence: 57%
“…Superoxide dismutase (SOD), as the primary ROS scavenger localizing in chloroplasts, mitochondria, peroxisomes and cytosol, catalyzes the disproportion of two O 2 • − radicals to H 2 O 2 and O 2 54 . Moreover, H 2 O 2 is scavenged by ascorbate-peroxidase (APX) in ascorbate-glutathione cycle and through guaiacol peroxidase (GP) and catalase (CAT) in cytoplasm and divided into water and oxygen 55 . The increased activity of the mentioned enzymes by TiO 2 treatments in the present study might be another reason for the observed decrease in H 2 O 2 values under salinity stress compared with control conditions.…”
Section: Assessment Of Biochemical Traits Evaluation Of Hydrogen Permentioning
confidence: 99%
“…Monoterpenes (mayor component in essential oils) were increased in plants exposed to 200 mg∙L −1 of TiO 2 NPs. Monoterpenes increase could be considered as a defense mechanism against free radicals generated by the NPs [ 207 ]. Meanwhile, Mentha piperita L. treated with 150 mg∙L −1 of TiO 2 NPs also showed an increase in essential oil contents by 105.1% compared to control.…”
Section: Plant Elicitorsmentioning
confidence: 99%
“…87,88 Various research groups have also investigated the elicitation potential of TiO 2 -NPs on plant SMs production using both in vivo and in vitro systems. [89][90][91] Using in vitro systems, aloin (118%) content was increased in cell suspension culture of Aloe vera when treated with TiO 2 NPs. 35 Similarly, the phenolic and avonoid contents in callus culture of Cicer arietinum were increased when exposed to different concentrations of TiO 2 NPs.…”
Section: Elicitation Potential Of Iron Oxide Nanoparticles (Fe 3 O 4 mentioning
confidence: 99%